Comparative analysis of flow patterns in off-design planar and conical nozzle - San L. Tolentino; Jorge Mírez (Ingenius: Revista de Ciencia y Tecnología)
This study aims to analyze the behavior of Mach number and pressure field flow patterns in off-design planar and conical nozzles with a divergent half-angle of 10.85°. Numerical simulations of the flow field were conducted using the ANSYS-Fluent R16.2 software, employing the RANS model and the SAS turbulence model under transient flow conditions. The nozzle pressure ratios (NPR) ranged from 1.97 to 8.91. The results reveal differences in flow patterns, including Mach number and static pressure, between the two nozzle types. Notably, normal shock fronts exhibited varying positions for the same NPR values. The maximum peak flow fluctuation along the centerline of the conical nozzle's divergent section reached Mach 2.844, compared to Mach 2.011 in the planar nozzle, indicating lower flow velocity in the latter. At the nozzle outlet, the flow velocity of the conical nozzle was Mach 2.535, representing a 27.32% increase compared to the planar nozzle, which achieved Mach 1.991. Additionally, the throat area significantly influenced mass flow transit, with the planar nozzle having a larger throat area than the conical nozzle. These findings provide insights into the impact of nozzle geometry on flow characteristics under off-design conditions.